2010
DOI: 10.20533/licej.2040.2589.2010.0032
|View full text |Cite
|
Sign up to set email alerts
|

Stylistics and Reader Response: An Integrated Approach to the Teaching of Literary Texts

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…More specifically, the last decade has seen several attempts to develop an integrative model towards literature teaching that would include the linguistic, cultural and personal elements. Worldwide linguistis and language teachers Timuchin (2001), Savvvidou 2004, Divsar (2009), and Dhanapal (2010) have thus questioned the traditional use of literature in the EFL classroom, offering a new and fresher integrated look at the way in which literary texts might be incorporated into the language classroom. Their approaches to literature teaching go as follows:…”
Section: Towards An Integrative Approach To Literature Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the last decade has seen several attempts to develop an integrative model towards literature teaching that would include the linguistic, cultural and personal elements. Worldwide linguistis and language teachers Timuchin (2001), Savvvidou 2004, Divsar (2009), and Dhanapal (2010) have thus questioned the traditional use of literature in the EFL classroom, offering a new and fresher integrated look at the way in which literary texts might be incorporated into the language classroom. Their approaches to literature teaching go as follows:…”
Section: Towards An Integrative Approach To Literature Teachingmentioning
confidence: 99%
“…In the same way, the communicative considerations set up the conditions for a crucial part of language learning consisting in an active interpretation of the text's meaning. Dhanapal's (2010) Integrated Approach. Dhanapal's Integrated Approach (2010) was implemented in the context of Malaysian high schools to enhance the students' development of critical and creative thinking skills (CCTS).…”
Section: Savvidoumentioning
confidence: 99%
“…For example, Carlisle (2000) studied the effect of creating reading logs on the participants' reading a novel while Gonzalez and Courtland (2009) explored how by the manipulation of the readerresponse approach for reading a Spanish novel, the participants could learn the language, appreciate the cultural values, and improve their metacognitive reading strategies. Dhanapal (2010) reported that using reader-response could enhance the participants' critical and creative thinking skills. Also, Khatib (2011) used the approach for enhancing EFL learners' vocabulary knowledge and reading skills though she could not find a statistically significant difference between the experimental and control groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach places equal importance on the study of language elements and on responding personally to poetry by integrating them to teach poetry in the EFL classroom with the Formeaning Response approach. Dhanapal (2010) assured that An integrated approach is an excellent approach to the teaching of literary text in the context as both stylistic and reader response are theories that blend well due to their natural characteristics of being extremely flexible but yet anchored in the sound theories of the established disciplines of linguistic and pragmatics.…”
Section: Modernismmentioning
confidence: 99%